BEHIND RUSSIA’S INVASION OF UKRAINE: THE CLASH OF DIFFERENT MODE OF CAPITALISM - Oktaviano, Nandito; Burhanuddin, Agussalim (Global: Jurnal Politik Internasional, 2023)
This research aims to analyse Russian foreign policy toward Ukraine from 2014 to 2022. It uses a dual logical plural approach from Marxist IR Theory. This approach greatly emphasises the importance of two systemic logics, namely capitalism and geopolitics. Since this approach is used in the realm of foreign policy analysis, contextualisation of the level analysis is needed. In this case, the dual logical plural approach proposes a distinctive description of these levels of analysis. International condition refers to the imperialism of the present world order, domestic factor refers to the development of state capitalism, and actors refer to the alliance of political elite and capitalist class of state. Based on those distinctive features, this research concludes several crucial points. First, the expansionist economic manoeuvre of the European Union and the imperialist manoeuvre of the US played crucial roles in affecting Russia's foreign policy toward Ukraine from 2014-2022. Second, the specific history of Russian capitalism development, which gave birth to the emergence of regressive Caesarism, also plays a significant role. Third, the development of Ukraine's capitalism and its class dynamics play a central role in navigating Russia's or Western states' manoeuvres. The dominance of Western Ukraine, which particularly articulates the interests of Ukraine's middle class and Western states' geopolitical or economic interests, significantly forces Russia to change the nature of its policy from annexation to invasion Keywords: American imperialism, European Union expansion, Russian capitalism, regressive caesarism